2007
DOI: 10.1007/s10826-007-9145-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Predictors of Disciplinary Style and Child Abuse Potential in a Hispanic and Anglo-American Sample

Abstract: Recent attention to multicultural issues has sparked recognition that parenting is also a culturally construed phenomenon. The present study involved a diverse sample of 90 Anglo-American and Hispanic parents examining predictors based on distal/proximal levels as conceptualized in the ecological model. The study examined background characteristics (e.g., minority status, educational level, income), intrapersonal (anger, parenting competence, parenting satisfaction), and extrapersonal (social support) factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…Although not significant in the final model (p = .06), correlation results also indicate that mothers receiving more support have a greater tendency to adopt attitudes less in favor of corporal punishment. Several comparable studies have found that a level of social support considered to be more satisfying diminishes the risk of physical abuse of the child, regardless of the family's ethnic origin (Rodriguez 2008). This is important since it appears that intervention intending to increase support from the partner and the social network has an impact on the mother's attitudes during the first year of the child's life (McCurdy 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not significant in the final model (p = .06), correlation results also indicate that mothers receiving more support have a greater tendency to adopt attitudes less in favor of corporal punishment. Several comparable studies have found that a level of social support considered to be more satisfying diminishes the risk of physical abuse of the child, regardless of the family's ethnic origin (Rodriguez 2008). This is important since it appears that intervention intending to increase support from the partner and the social network has an impact on the mother's attitudes during the first year of the child's life (McCurdy 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the absence of several factors such as the father's point of view (Flynn 1998), the form and severity of the violence the mothers experienced as children (Clément and Bouchard 2003;Deater-Deckard et al 2003), religious affiliation (Gershoff et al 1999;Jackson et al 1999) and ethnic origin (Deater-Deckard et al 2003;Flynn 1998;Straus and Stewart 1999). We might also consider the factors of empathy, personality traits, and the parents' psychological characteristics (i.e., symptoms of depression) (Leung and Smith-Slep 2006;Perez-Albeniz and De Paul 2003;Rodriguez 2008). Lastly, the mothers' responses in this kind of survey are inevitably subject to the bias of social desirability in spite of the precautions we took during the study in order to diminish its impact.…”
Section: Discussionmentioning
confidence: 99%
“…A sample item is, ''I am delighted with the relationship that I have with my children''. As with the CAIR, we utilized raw scores (e.g., see Rodriguez 2008). The PSS has evidence of convergent validity with other measures of life satisfaction and subscale content consistency (Cleminshaw and Guidibaldi 1985).…”
Section: Mothers' Self-report Measuresmentioning
confidence: 99%
“…Various internalizing problems are linked to later child maltreatment, including low self-esteem (Christensen, Brayden, Dietrich, McLaughlin, & Sherrod, 1994; Whipple & Webster-Stratton, 1991) and depression (Chaffin et al, 1996; Ethier et al, 1995; Whipple & Webster-Stratton, 1991), as well as a history of psychopathology and severe mental illness (Brown et al, 1998; Chaffin et al, 1996; Stith et al, 2009). Externalizing behaviors, including alcohol and drug use (Chaffin et al, 1996; Kelleher, Chaffin, Hollenberg, & Fischer, 1994; MacMillan, 2000); criminal behavior (Altemeier et al, 1982); and anger expression, verbal aggression, and hostility (DiLalla & Crittenden, 1990; Rodriguez, 2008; Schumacher, Feldbau-Kohn, Smith Slep, & Heyman, 2001; Simons & Whitbeck, 1991; Stith et al, 2009) have also been associated with later maltreatment. It should be noted that, although these factors are likely to have emerged in childhood or adolescence, the majority of these studies identified and measured them retrospectively in adulthood.…”
Section: Previous Studiesmentioning
confidence: 99%